Prospects for Selecting Wheat with Increased Zinc and Decreased Cadmium Concentration in Grain. Issue 4 (1st July 2015) - Guttieri, Mary J.; Baenziger, P. Stephen; Frels, Katherine; Carver, Brett; Arnall, Brian; Wang, Shichen; Akhunov, Eduard; Waters, Brian M.
ABSTRACT: Wheat ( Triticum aestivum L.) is a primary staple cereal and significant source of mineral nutrients in human diets. Therefore, increasing concentration of the essential mineral, Zn, and decreasing concentration of the toxic mineral, Cd, could significantly improve human health. Because plant mechanisms for uptake and translocation of Cd and Zn are related, we assessed both Cd and Zn concentration to evaluate their independence in hard winter wheat germplasm. Grain Cd concentrations of some genotypes grown in Nebraska trials were above the Codex guidance level (0.2 mg kg –1 ), and highly repeatable differences in grain Cd were found between pairs of low and moderate‐Cd commercial cultivars. Grain Cd concentration was predicted by Cd concentration in aboveground plant tissues at anthesis. However, grain Zn concentration was not predicted by Zn concentration in aboveground plant tissues. Genome‐wide association scans using high‐density single nucleotide polymorphism (SNP) markers identified Cd‐associated SNPs on 5AL in a region homoeologous to the Cdu1 locus on 5BL in durum wheat ( Triticum turgidum L. var. durum Desf.). Genetic regulation of grain cadmium concentration in bread wheat may be more complex than in durum wheat because epistatic interactions between SNP markers were identified, and SNP marker haplotypes were imperfect predictors of grain Cd phenotype. The SNP marker associations with Zn concentration were weak and inconsistent across trials, and Zn concentration was independent of 5AL markers. The independent genetic regulation of grain Cd and Zn concentrations indicates that breeding low Cd hard winter wheat genotypes without reducing Zn concentration has high potential for success.